ONCE AGAIN IUSTUS ERROR AND SURETYSHIPS Absa Bank Ltd v Trzebiatowsky 2012 (5) SA 134 (ECP) - C-J Pretorius (Obiter, 2021)
In Absa Bank Ltd v Trzebiatowsky (2012 (5) SA 134 (ECP)) the court was faced with a defence that has become all too common within the context of suretyship agreements, namely that of iustus error, or rather material and reasonable mistake rendering the contract void. Traditionally the courts have been wary of releasing a signatory of a contractual document from liability in the absence of some form of misrepresentation on the part of the contract assertor, but in Brink v Humphries & Jewell (Pty) Ltd (2005 (2) SA 419 (SCA)) the Supreme Court of Appeal adopted a far more lenient approach, one which opened the door for potential abuse of this defence, especially it seems so where suretyships are involved. The Trzebiatowsky decision is relevant for confirming the more traditional approach as opposed to the one largely ushered in by Brink and for sensibly reflecting the issues relevant to adjudicating these cases.